Tanggung Jawab Pt. Putra Bone Riau Mandiri Terhadap Keamanan Dan Keselamatan Penumpang Di Pelindo I Cabang Tembilahan Kabupaten Indragiri Hilir Berdasarkan Undang Undang Nomor 17 Tahun 2008 Tentang Pelayaran - Syahrensyah Syahrensyah; Maryati Bachtiar; Setia Putra (Jurnal Ilmiah Wahana Pendidikan, 2026)
Indonesia as an archipelagic country has thousands of large and small islands separated by oceans, so that sea transportation plays an important role in supporting human mobility and distribution of goods between regions. So that the implementation of sea transportation activities can be carried out in an orderly manner and protect the interests of all parties involved in it. Case study at PT. Putra Bone Riau Mandiri as a transportation service provider focuses on the issue of responsibility to passengers when an accident occurs. The main problem has occurred the Speed ​​​​Boat Evelyn Calisca 01 accident under the auspices of PT. Putra Bone Riau Mandiri located in the waters of the Guntung River, Due to the accident, 12 (twelve) passengers of the Speed ​​​​Boat were found dead and 51 (fifty-one) passengers and crew of the Speed ​​​​Boat were found safe. This objective is to find out whether the PT's responsibility exists and how the appropriate responsibility is given by PT. Putra Bone Riau Mandiri. The results of this study explain the implementation of PT. Putra Bone Riau Mandiri's Responsibility for passengers who were victims, therefore the PT provided a sum of money for passengers who had become victims of the accident that befell the Speed ​​Boat Evelyn Calisca 01, hereby PT. Bone Riau Mandiri provides responsibility in the form of money by making payments in one month 2 (two) times the payment in the form of a sum of money determined by PT. Putra Bone Riau Mandiri amounting to 50 million (fifty million) for those who died and those who survived with a total of 20 million (twenty million) for those who survived. This is regulated in Article 10 of Law Number 17 of 2008 concerning Shipping, which confirms that the ship is in seaworthy condition and meets safety standards. This includes carrying out routine maintenance and inspections to ensure the ship is always in good condition. If there is a violation of safety standards, the company can be asked to be legally responsible and provide compensation to the victim.